Alemtuzumab (Campath-1H) experience in kidney transplantation what we have learned; current practices; and scope for the future?. Issue 6 (December 2015) - Gundroo, Aijaz; Zachariah, Mareena; Singh, Neeraj; Sharma, Rajeev
Abstract : Purpose of review: Alemtuzumab (Campath) usage as a preconditioning agent in kidney transplantation has gained considerable interest in the recent future. Alemtuzumab is currently available only by special request from Sanofi through its Campath distribution program. It is restricted to transplant programs with prior and continued experience with the agent. There may be a resurgence of interest for the utilization of this agent because of its ease of administration, and less cost and comparable or improved outcome in comparison to other induction agents. Recent findings: Alemtuzumab when combined with standard calcineurin inhibitor and mycophenolate mofetil is well tolerated and efficacious as an induction therapy and allows for long-term steroid avoidance in high-risk renal transplant recipients. Summary: The transplant community has advanced through a learning curve with the use of alemtuzumab over time; starting from an agent that was tried out to induce proper tolerance, minimization of nephrotoxic calcineurin inhibitors, and currently as a comparable depletional therapy that can reduce acute rejection in high-risk kidney transplant recipients.